Perspectives of children and adolescents with cerebral palsy about involvement as research partners: a qualitative study. Issue 16 (31st July 2022) - Cavens, C.; Imms, C.; Drake, G.; Garrity, N.; Wallen, M.
Abstract: Purpose: Children and adolescents with cerebral palsy have diverse needs and often engage with healthcare services, including paediatric rehabilitation. Partnering with these children and adolescents on research projects to inform practice has the potential to ensure services continue to remain relevant and appropriate. This study aimed to identify what children and adolescents with cerebral palsy suggest are effective ways for researchers to involve them as partners in research. Materials and methods: This qualitative study was guided by interpretive description. Children and adolescents with cerebral palsy between 8 and 18 years participated in semi-structured, activity-based focus groups or interviews. Verbatim transcripts were coded and analysed using thematic analysis. One member of the research team was a young woman with cerebral palsy. Results: Seventeen children and adolescents with cerebral palsy from NSW and Victoria (Australia) were involved. Participants were between 8 and 18 years (mean = 12 years), male ( n  = 11) and female ( n  = 6). Analysis identified four nested themes: "insider knowledge", " reasons for involvement", "roles in research" and "facilitating partnership" . Conclusion: This study identified perspectives of children and adolescents on their involvement as research partners, and considerations for researchers to facilitate involvement of children and adolescents with cerebral palsy as partners in research. IMPLICATIONS FOR REHABILITATION: The commitment in healthcare to client-centred practice requires that consumers, including children and young people with cerebral palsy, have opportunities to influence the direction of research which impacts them. Children and young people with cerebral palsy are interested in research partnerships and motivated to be involved in various areas of research. Effective research partnerships with younger populations can be facilitated by researchers acknowledging a child or young person's expertise, and employing strategies relating to open communication, flexibility and support.